The Application on the Clinical Practice Pathway Checklist of Narrative Medicine of Traditional Chinese Medicine: A Case Study on Glaucoma Treatment - Yipin LIU; Shaoyan LIU; Jingjing ZHAO; Jie LI; Zixu WANG (Yixue yu zhexue)
In response to the practical challenges of communication between clinicians and patients in Traditional Chinese Medicine (TCM), and to support the localization of narrative medicine practices, this paper introduces four clinical practice pathway checklists for TCM narrative medicine: the listening elements checklist, the root-branch-priority checklist, the tripartite plan-making checklist, and the root-branch-priority record (patient version). For clear explanation of four checklists, this paper uses glaucoma diagnosis and treatment as an example to elaborate the application scenarios, usage methods, procedures, and precautions for each checklist from two aspects: instructions for use and application demonstration. This aims to assist clinicians in more efficiently collecting patient stories and evidence-based data during communication, thereby improving the quality of care. Additionally, the root-branch-priority record (patient version) is the record in a patient-centered manner for aiding patients to record their physical and mental conditions, which helps to enhance patient engagement and improve doctor-patient communication.